Effectiveness of endolymphatic duct blockage versus endolymphatic sac decompression in patients with intractable Ménière’s disease: study protocol for a double-blinded, randomised controlled trial - Stefan Böhringer; Suzanne C Cannegieter; Wilbert B van den Hout; Sebastiaan Hammer; Annejet A Schenck; Josephina M Kruyt; Peter Paul van Benthem; Susan P M Hombergen; Henk M Blom (BMJ Open)
Introduction Outcomes of surgery for Ménière’s disease (MD) remain discordant. Recently, a new surgical procedure in which the endolymphatic duct is clipped was proposed. To date, only one prospective trial assessing this technique was published, yielding promising results. This protocol describes a prospective, double-blinded, randomised controlled trial that will be carried out to assess the effectiveness of this surgical intervention.Methods Eighty-four patients with intractable MD will be recruited from 13 hospitals in the Netherlands. Intraoperatively, randomisation will determine whether endolymphatic duct blockage (EDB) or endolymphatic sac decompression (ESD) will be performed. Randomisation will be 1:1 stratified for gender and duration of MD (recent-onset versus mature MD). All participants receive vestibular rehabilitation after surgery. Patients are followed up during 1 year after surgery. Follow-up visits will take place at 1 week, 3 months, 6 months and 12 months after surgery. The main study endpoint is proportion of patients who are free of vertigo spells at 12 months postoperatively. Secondary parameters include cumulative number of vertigo bouts, co-intervention, tinnitus, hearing, quality of life, cost effectiveness and a budget impact analysis. Total duration of the study is 4 years.Analysis The primary analysis will follow the intention-to-treat principle. For the primary outcome, a χ2 test will be performed. Secondary outcomes will be analysed using a linear mixed model (EDB versus decompression group) at the different time measurement point.Ethics and dissemination This study was reviewed and approved by a board of specialists before funding was obtained, as well as by the Medical Research Ethics Committee Leiden-The Hague-Delft and the boards of all participating centres. Results of this study will be published in international peer-reviewed scientific journals and will be presented on (inter)national scientific conferences and meetings.Trial registration numbers NL9095 and ISRCTN12074571; Pre-Results.